Impact of Antiarrhythmic Drugs on the Outcome of Short QT Syndrome - El-Battrawy, Ibrahim; Besler, Johanna; Li, Xin; Lan, Huan; Zhao, Zhihan; Liebe, Volker; Schimpf, Rainer; Lang, Siegfried; Wolpert, Christian; Zhou, Xiaobo; Akin, Ibrahim; Borggrefe, Martin (Frontiers in Pharmacology, 2019)
Abstract Short QT Syndrome (SQTS) is associated with sudden cardiac arrest (SCA). There is limited data on the impact of antiarrhythmic drugs on the outcome of SQTS. Material and Methods We studied data describing the clinical outcome of 62 SQTS patients treated with antiarrhythmic drugs, recruited from a pool of patients diagnosed in our institution and also from known databases after a systematic search of published literature. Results 62 SQTS patients treated with anti-arrhythmic drugs were followed up over a median timeframe of 5.6 years (1.3-4.1 years). 6 patients in particular, received multiple drugs as a combination. Out of 55 patients treated with hydroquinidine (HQ) the long-term prophylaxis was documented in 41 patients. 14 patients stopped the treatment for the following reasons: gastrointestinal intolerance (n=4), poor compliance (n=8), and no QTc prolongation (n=2). Of the 41 patients with HQ the QTc interval increased from 313.5±17.2 ms to 380.1±21.2 ms. 13/41 of the patients suffered at least 1 or more ventricular arrhythmia (VA) before HQ initiation. VAs are reduced in incidence after HQ treatment (13/41: 31% versus 3/41: 7.3%, p<0.001). Conclusion HQ increases the corrected QT interval and prevents VAs in the majority of patients in this cohort. HQ is safe for use in SQTS patients particularly with its low rate of side effects. Other antiarrhythmic drugs might be useful, but the data justifying their use are sparse.